New insights towards an integrated understanding of NE Asian monsoon during mid to late Holocene. (15th February 2021) - Zhao, Jingyao; Tan, Liangcheng; Yang, Yan; Pérez-Mejías, Carlos; Brahim, Yassine Ait; Lan, Jianghu; Wang, Jian; Li, Hanying; Wang, Tianli; Zhang, Haiwei; Cheng, Hai
Abstract: Speleothem records from NE Asia are essential to understand the spatial patterns of the Asian Summer Monsoon (ASM) variability. In this paper, we present a new high-resolution and chronologically well-resolved speleothem record from Liu-li (LL) cave, NE China, through δ 18 O, δ 13 C and Sr/Ca ratio characterizing a dynamic ASM history over the past 6680 years. The LL δ 18 O record shows a long-term trend to higher values, following the North Hemisphere summer insolation (NHSI), with the exception of the last 2 kyr characterized by a negative δ 18 O excursion. The '2-kyr shift' is evident in NE Asia over the past 2 kyr, originally inferred from the speleothem δ 18 O negative excursion in South China, as well as in many other proxy records from East China, but it merely manifests a flat trend in most of the western East Asian Summer Monsoon (EASM) and Indian Summer Monsoon (ISM) regions, rather than a negative excursion. On multi-centennial to millennial timescales, the intensification of the Tsushima Warm Current (TWC) can amplify rainfall on both sides of the Japan Sea. A close comparison between the monsoon reconstruction and the cultural changes in NE Asia suggests contemporary climatic and cultural regime-shifts, implying an important role of the ASM weakening in the collapse of Neolithic and Early Bronze cultures in this region. Highlights: The records we present and the comparison with many regional paleoclimate records offers new evidences of the distribution of the '2-kyr shift'. On multi-centennial to millennial timescales, the covariation of different records in NE Asia suggests that the intensification of the Tsushima Warm Current can amplify rainfall on both sides of the Japan Sea. The contemporary climatic and cultural regime-shifts suggest that the monsoon weakening might play an important role in the collapse of the Neolithic and Early Bronze cultures from this region.